2015
DOI: 10.1186/s13148-015-0160-7
|View full text |Cite
|
Sign up to set email alerts
|

CpG island methylation profile in non-invasive oral rinse samples is predictive of oral and pharyngeal carcinoma

Abstract: BackgroundThere are currently no screening tests in routine use for oral and pharyngeal cancer beyond visual inspection and palpation, which are provided on an opportunistic basis, indicating a need for development of novel methods for early detection, particularly in high-risk populations. We sought to address this need through comprehensive interrogation of CpG island methylation in oral rinse samples.MethodsWe used the Infinium HumanMethylation450 BeadArray to interrogate DNA methylation in oral rinse sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…This study adopted a different approach from 450k methylation arrays to interrogate a set of genes already known to be altered in HNSCC [ 5 , 15 , 19 , 20 , 27 ]. For in-depth investigation of the true methylation level, we developed a novel accurate, sensitive, and specific assay to detect early OSCC and HGSIL from oral brushing specimens using bisulfite NGS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study adopted a different approach from 450k methylation arrays to interrogate a set of genes already known to be altered in HNSCC [ 5 , 15 , 19 , 20 , 27 ]. For in-depth investigation of the true methylation level, we developed a novel accurate, sensitive, and specific assay to detect early OSCC and HGSIL from oral brushing specimens using bisulfite NGS.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ZAP70 , KIF1A , GP1BB , and MIR137HG were previously described to be differentially methylated in OSCC by our group [ 15 ] and others [ 5 , 18 , 19 ], while PAX1 , LRRTM1 , PARP15 , FLI1 , NTM , LINC00599 , EPHX3 , and ITGA4 were discovered by Guerrero-Preston et al [ 20 ]. Additionally, the remaining MIR193A , MIR296 , TERT , TERC , H19 , DNMT1A , and LINE1 were found to be epigenetically altered in OSCC by various authors [ 21 27 ] (see Table 2 for details).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the potential use of DNA methylation analysis of one or a combination of genes has been investigated as a prognostic marker in head and neck squamous cell carcinoma based on non-invasive sampling collection [9,11,13,14,16,18,[44][45][46][47][48]; however, the majority of these studies found that an altered methylation level was related to poor prognosis and the samples were collected at the time of OSCC diagnosis (pretreatment). The prognostic value of promoter hypermethylation was identified for one gene in a pattern of genes from post-operative saliva samples.…”
Section: Discussionmentioning
confidence: 99%
“…CpG dinucleotides are highly accumulated in the 5′ promoter region of genes referred as CpG islands, which are unmethylated in transcriptionally active genes. Once CpG islands become methylated, transcriptional repression occurs [ 27 ].…”
Section: Epigenetic Mechanisms In Cancermentioning
confidence: 99%